Religious, Social and Political Factors Impacting Islamic Denominations - Shirinov, Agil; Ağamoğlanov, Hilal (Scholarya Demo Journal of Ruby, 2019)
After the death of the Prophet Muhammad, different views among Muslims led to the differences based on sectarian and denominationalizing tendencies. Socio-political and cultural changing caused many people to unite around certain thoughts and thinkers. The early disagreement on the caliphate as well as the protests initiated during the reign of the caliph ʿUthmān ibn ʿAffān and the battles in the name of revenge for his blood after his assassination increased political fractionalization in society and led to the emergence of Kharijite groups. The Umayyads’ policies also led to the discussions over some theological problems like Jabr and Qadar (predestination and free will) and to disagreements on those issues. At the same time, the Umayyads’ unfair attitude towards Mawali (non-Arab Muslims) caused many revolts against the Caliphate. In the Abbasid period, the differences of thought over some issues, like Khalq al-Qur’an, between various Islamic denominations deepened as well as a number of religious denominations strengthened their positions by gaining the support of State authorities and different sections of society.